2016
DOI: 10.1088/0957-4484/27/14/145202
|View full text |Cite
|
Sign up to set email alerts
|

Shape manipulation of ion irradiated Ag nanoparticles embedded in lithium niobate

Abstract: Spherical silver nanoparticles were prepared by means of ion beam synthesis in lithium niobate. The embedded nanoparticles were then irradiated with energetic (84)Kr and (197)Au ions, resulting in different electronic energy losses between 8.1 and 27.5 keV nm(-1) in the top layer of the samples. Due to the high electronic energy losses of the irradiating ions, molten ion tracks are formed inside the lithium niobate in which the elongated Ag nanoparticles are formed. This process is strongly dependent on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
0
20
0
2
Order By: Relevance
“…For instance, elongation of metallic nanoparticles using SHIs has been reported for cobalt NPs implanted in SiO 2 and irradiated with iodine 31 , for gold NPs implanted in planar SiO 2 films after irradiation with Si 32 and Cu 33 ions and Pt NPs formed by ion-beam synthesis in amorphous SiO 2 irradiated with Au ions 34 . More recently, there are also several works reporting the use of swift heavy ions to elongate Ag 35, 36 , Au 3740 , Zn 41, 42 , and Ni 43 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, elongation of metallic nanoparticles using SHIs has been reported for cobalt NPs implanted in SiO 2 and irradiated with iodine 31 , for gold NPs implanted in planar SiO 2 films after irradiation with Si 32 and Cu 33 ions and Pt NPs formed by ion-beam synthesis in amorphous SiO 2 irradiated with Au ions 34 . More recently, there are also several works reporting the use of swift heavy ions to elongate Ag 35, 36 , Au 3740 , Zn 41, 42 , and Ni 43 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the realization of elongation requires several basic conditions as follows: the high enough energy (hundreds of MeV) and proper fluence (≈10 13 ions cm −2 ) of implanted ions to form the ion tracks in the dielectrics; the larger diameter of NPs than the width of tracks (usually larger than 10 nm); and the suitable dielectrics. [ 90–102 ] It should be noted that the size condition of NPs for elongation is still under debate; and some experimental and theoretical studies on smaller NPs for effective elongation have been reported. [ 81 ] In this way, the NP–dielectrics systems can be well designed with tunable physical properties by optimizing the parameters during ion beam processing.…”
Section: Ion Beam Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…The direct implantation of Si ions can be used to synthesize NPs with spherical geometries in dielectrics. By the use of swift heavy ion irradiation, the nanostructures can be reshaped, thus elongating the spherical NPs in the thin films [12][13][14][15]. The concentration of NPs can be controlled by the ion dose.…”
Section: Introductionmentioning
confidence: 99%